Smart Speaker im Lichte der StPO Möglichkeiten des Zugriffs und Problematiken der Verwertbarkeit - Gallus, Nico (Beiträge zum Strafrecht - Contributions to Criminal Law, 2022)
Smart speakers are now ubiquitous in the everyday lives of millions of citizens. Regarding current considerations to use smart speakers in the context of law enforcement, it is only a matter of time until they will also be dealt with by the highest courts. This dissertation examines to what extent smart speakers can be used for criminal prosecution under current law. It outlines the practical problems of accessing data generated by smart speakers, the degree to which such access can be reconciled with the case law already been handed down, and the constitutional law and criminal procedure aspects that have to be considered in the context of the usability of such data.